2007
DOI: 10.1111/j.1439-0531.2006.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dynamics in Heifers during Pre‐pubertal and Pubertal Period Kept under Two Levels of Dietary Energy Intake

Abstract: The objective of this study was to characterize follicular dynamics in pre-pubertal, pubertal and post-pubertal periods, as well as the effect of high-energy intake on follicular development and age at puberty in heifers. Thirty-one Nelore (Bos indicus) heifers, 6 months old, were randomly assigned to receive two different diets: one of low (GI) and other of high dietary energy intake (GII). Animals were evaluated in relation to body weight gain by being weighed every 21 days. Heifers were evaluated every othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
1
6
0
14
Order By: Relevance
“…Puberty in heifers was defined by plasma progesterone concentration, ultrasound images of corpus luteum (CL) and detection of oestrous (Shamay et al 2005;Romano et al 2007;Johnston et al 2009). Puberty in bulls was defined by scrotal circumference thresholds and was related to sperm concentration, motility and morphology (Lunstra et al 1978;Bagu et al 2004;Siddiqui et al 2008;Corbet et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Puberty in heifers was defined by plasma progesterone concentration, ultrasound images of corpus luteum (CL) and detection of oestrous (Shamay et al 2005;Romano et al 2007;Johnston et al 2009). Puberty in bulls was defined by scrotal circumference thresholds and was related to sperm concentration, motility and morphology (Lunstra et al 1978;Bagu et al 2004;Siddiqui et al 2008;Corbet et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the lower proportion of Nellore-sired heifers detected in estrus might be due to difficulty observing behavioral estrus. However, a recent study from Brazil using serum progesterone concentrations instead of behavioral estrus to identify first ovulation in Nellore heifers reported age at puberty at 510 -540 days of age (Romano et al, 2007). Accounting for differences due to location, management practices and heterosis in the Germplasm Evaluation Project, these data support an advanced age at puberty in the Nellore breed.…”
Section: Age At Pubertymentioning
confidence: 83%
“…Therefore, WSF heifers presented puberty at a greater weight and younger age than NSF ones (Table 1). The benets of improved heifer feeding on weight gain and age at puberty have been documented in Bos taurus (Gasser et al 2006d), Bos indicus (Romano et al 2007) and Bos taurus x Bos indicus breeds ). An early increase in the frequency of LH pulses, larger follicles, a higher number of follicular waves, greater estrogen secretion, greater weight, and lower age at puberty have been observed in Bos taurus heifers supplemented with feed (Gasser et al 2006a(Gasser et al , 2006b(Gasser et al , 2006c.…”
Section: Changes In Body Weightmentioning
confidence: 99%